T cell responses to control fungal infection in an immunological memory lens - Sharma, Jaishree; Mudalagiriyappa, Srinivasu; Nanjappa, Som Gowda (Frontiers in Immunology, 2022)
In recent years, fungal vaccine research emanated significant findings in the field of antifungal T cell immunity. The generation of effector T cells is essential to combat many mucosal and systemic fungal infections. The development of antifungal memory T cells is integral for controlling or preventing fungal infections, and understanding the factors, regulators, and modifiers that dictate the generation of such T cells is necessary. Despite the deficiency in the clear understanding of antifungal memory T cell longevity and attributes, in this review, we will compile some of the existing literature on antifungal T cell immunity in the context of memory T cell development against fungal infections.